Fuzzy decision trees as a decision-making framework in the public sector - Benčina, Jože (Yugoslav Journal of Operations Research, 2011)
Systematic approaches to making decisions in the public sector are becoming very common. Most often, these approaches concern expert decision models. The expansion of the idea of the development of e-participation and e-democracy was influenced by the development of technology. All stakeholders are supposed to participate in decision making, so this brings a new feature to the decision-making process, in which amateurs and non-specialists are participating decision making instead of experts. To be able to understand the needs and wishes of stakeholders, it is not enough to vote for alternatives - it is important to participate in solution-finding and to express opinions about the important elements of these matters. The solution presented in this paper concerns fuzzy decision-making framework. This framework combines the advantages of the introduction of the decision-making problem in a tree structure and the possibilities offered by the flexibility of the fuzzy approach. The possibilities of implementation of the framework in practice are introduced by case studies of investment projects appraisal in a community and assessment of efficiency and effectiveness of public institutions.